Keterampilan Pemecahan Masalah Berbasis Model Experiential Learning - Tuti Hendriyani; Carolina Ligya Radjah; Arbin Janu Setiyowati (Graduate School of Universitas Negeri Malang, 2020)
Abstract: This study aims to produce guidance products that have acceptance criteria. The type of research used is development using the research design of Borg and Gall. The stages used in this research are information gathering, planning, initial field testing, developing the initial product format, product revision, main field testing, and product revision or refining the main field test results. The data obtained in the form of quantitative data with the gregory model interrater agreement. The subjects in the field test consisted of two BK experts, two media experts, and two potential product users. The assessment conducted by the expert refers to the criteria for product acceptance which includes aspects of accuracy, aspects of usability, and aspects of eligibility. Based on the results of the field test the assessment results obtained from BK experts have a validity index of 0.73 which is categorized as